Determination and interpretation of changes in thermophysical properties of a carbon-fibre prepreg during cure. (February 2016) - McHugh, Jarlath; Stark, Wolfgang
Abstract: Epoxy composites used for high-end structural applications are typically cured under the influence of temperature and pressure causing a number of complex chemical and physical transformations. On heating a mould, temperature gradients will occur through the component which will depend largely on the thermophysical properties of the specific composite. The crosslinking reaction is exothermic leading to additional heat release, thus complicating heat transportation models. If such effects are not accounted for, it can lead to variations in resin flow, poor fibre wetting causing voiding and inhomogeneous cure, leading to shrinkage and unfavourable variations in moulded part geometry. Limited information is available for thermal models used in the manufacture of reinforced thermosets. Autoclave [1, 2] and laser or infra-red curing processes [3, 4] typically use constant values determined on fully cured parts. In this work, the variation in thermal conductivity (K) (W/(m K)), thermal diffusivity (a) (m 2 /s) and specific heat capacity at constant pressure (cp ) (J/(g K) is determined for a carbon fibre prepreg during cure. It is the intention to improve understanding of how these parameters are related to chemical or physical transformations occurring during cure, and where estimates or shortcuts may be used for heat transfer models.